Resource Provision Scheduling in Cloud using Game Theory - Kaur, Gagandeep (International Journal of Computer Sciences and Engineering, 2019)
In cloud computing environment, resource allocation problem identifies that the cloud provider expects profit and the users expects best resources by considering budget and time constraints. In this paper, game theory mechanism has been used and an auction-based method is proposed which determines the auction winner and holding a repetitive game with incomplete information in a non-cooperative environment. In the proposed method, users calculate suitable price bid with their objective function during several round and repetitions and send it to the auctioneer; and the auctioneer chooses the winning player based on the suggested utility function. In the proposed technique, the end point of the game is the Nash equilibrium point where players are no longer inclined to alter their bid for that resource and the concluding bid also satisfies the auctioneer’s utility function. The proposed model is simulated in the Cloudsim and the results are compared with previous work.